2018
DOI: 10.1038/s41398-018-0124-8
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic risk for schizophrenia and measured domains of cognition in individuals with psychosis and controls

Abstract: Psychotic disorders including schizophrenia are commonly accompanied by cognitive deficits. Recent studies have reported negative genetic correlations between schizophrenia and indicators of cognitive ability such as general intelligence and processing speed. Here we compare the effect of polygenetic risk for schizophrenia (PRSSCZ) on measures that differ in their relationships with psychosis onset: a measure of current cognitive abilities (the Brief Assessment of Cognition in Schizophrenia, BACS) that is grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 62 publications
5
48
1
Order By: Relevance
“…GWAS studies have found a significant genetic overlap between cognition and schizophrenia [18][19][20] , and a recent study by Toulopoulou et al 21 showed that the variance in schizophrenia liability explained by PRS was partially mediated through cognitive deficit.…”
Section: Introductionmentioning
confidence: 99%
“…GWAS studies have found a significant genetic overlap between cognition and schizophrenia [18][19][20] , and a recent study by Toulopoulou et al 21 showed that the variance in schizophrenia liability explained by PRS was partially mediated through cognitive deficit.…”
Section: Introductionmentioning
confidence: 99%
“…The composite score of the CMINDS, applied by Nakahara et al [27] , also showed a significant negative correlation between SZ-PRS and general cognitive abilities. Further reviewed studies have not been able to show a significant association between SZ-PRS and general cognitive abilities in cases [29,35] . Interestingly, Shafee et al [29] found a significant association between general cognitive abilities and SZ-PRS in the non-psychiatric group.…”
Section: General Cognitive Abilitiesmentioning
confidence: 87%
“…Interestingly, Shafee et al [29] found a significant association between general cognitive abilities and SZ-PRS in the non-psychiatric group. Therefore, they assumed that cognitive decrease in patients was due to morbid factors like disease progression, protective effects, treatment effects and possible substance abuse [29] .…”
Section: General Cognitive Abilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The SZ PRS has been linked with prodromal motor deficits (7), as well as cognitive decline lower educational attainment in the general population (8,9). However, it is unclear whether SZ PRS predicts either cognition or cognitive decline in people with psychotic disorders (10).…”
Section: Introductionmentioning
confidence: 99%